2022
DOI: 10.26508/lsa.202201583
|View full text |Cite
|
Sign up to set email alerts
|

Trans-differentiation of trophoblast stem cells: implications in placental biology

Abstract: Trophoblast invasion is a hallmark of hemochorial placentation. Invasive trophoblast cells replace the endothelial cells of uterine spiral arteries. The mechanism by which the invasive trophoblast cells acquire this phenotype is unknown. Here, we demonstrate that, during differentiation, a small population of trophoblast stem (TS) cells trans-differentiate into a hybrid cell type expressing markers of both trophoblast (TC) and endothelial (EC) cells. In addition, a compendium of EC-specific genes was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Trophoblast cellinduced de-differentiation leads to phenotypic switching in VSMCs that involve suppression of contractile markers expression and elevation of synthetic state markers (Nandy et al, 2020) Previous studies demonstrated that trophoblast cells isolated from first trimester human placenta expressed membrane-associated TRAIL and induced apoptosis of human aortic VSMC (Keogh et al, 2007). Expression of TRAIL in trans-differentiated trophendothelial cells was demonstrated by our laboratory (Paul et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Trophoblast cellinduced de-differentiation leads to phenotypic switching in VSMCs that involve suppression of contractile markers expression and elevation of synthetic state markers (Nandy et al, 2020) Previous studies demonstrated that trophoblast cells isolated from first trimester human placenta expressed membrane-associated TRAIL and induced apoptosis of human aortic VSMC (Keogh et al, 2007). Expression of TRAIL in trans-differentiated trophendothelial cells was demonstrated by our laboratory (Paul et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies demonstrated that trophoblast cells isolated from first trimester human placenta expressed membrane‐associated TRAIL and induced apoptosis of human aortic VSMC (Keogh et al, 2007). Expression of TRAIL in trans‐differentiated trophendothelial cells was demonstrated by our laboratory (Paul et al, 2022). Our observation that RNA interference of PRNP in VSMCs caused apoptotic death led to our hypothesis that PRNP protects VSMCs from apoptotic cell death.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations